Strategy Analysis of Development of Traditional Herbs SMEs during the Covid-19 Pandemic in Jember District - Dewi Deniaty Sholihah; Alfiandi Imam Mawardi (Enrichment : Journal of Management, 2022)
The condition of the COVID-19 pandemic has pushed Indonesian consumers to demand herbal food and drinks as one of the anticipations of preventing the transmission of the COVID-19 virus. This provides a breath of fresh air for traditional herbal medicine entrepreneurs. Jamune Buk Woels in Jember Regency is present as an MSME who sees and takes advantage of the situation in Indonesia during the COVID-19 pandemic. This study aims to identify and examine the internal and external factors of Jamune Buk Woels, consider the determinants of the success of Jamune Buk Woels and formulate an effective marketing strategy that can be applied to the Jamune Buk Woels MSME market. The results showed that the Jamune Buk Woels MSME business development strategy was to apply an aggressive strategy, namely cooperating and partnering with MSME development agencies or institutions to help obtain business capital. Jamune Buk Woels needs to make efforts to improve the quality and quality of products, rebrand and market products with digital marketing. In addition, Jamune Buk Woels can empower housewives around so that it can increase the opportunities for opening up employment opportunities.